MATHEMATICS
HIGH SCHOOL

Answer: The quadratic formula is the result of completing the square for ax^2+bx+c=0 when a,b, and c are unknown values. This result is:

x=(-b±√(b^2-4ac))/(2a), we have x^2-x-2=0 so

x=(1±√(1+8))/2

x=(1±√9)/2

x=(1±3)/2

x=-1 and 2

x=(-b±√(b^2-4ac))/(2a), we have x^2-x-2=0 so

x=(1±√(1+8))/2

x=(1±√9)/2

x=(1±3)/2

x=-1 and 2

HIGH SCHOOL

Define the term ratio.

The quantitive relation between two amounts showing the number of times ones value contained or is contained within the other.

Answer:

Step-by-step explanation:

IT SHOWS THE RELATIVE SIZE BETWEEN 2 OR MORE NUMBERS.

MIDDLE SCHOOL

Least to greatest.

15 3/4, 16.3, 15.4, 16 1/4

The answer is 15.4, 15 3/4, 16 1/4, 16.3.

You can convert all numbers to decimal form to make it easier on yourself. For example, 15 3/4 = 15.75, which is greater than 15.4.

Hope that helped you.

You can convert all numbers to decimal form to make it easier on yourself. For example, 15 3/4 = 15.75, which is greater than 15.4.

Hope that helped you.

HIGH SCHOOL

please help me with this math problem: Alice has 1/5 as many miniature cars as Sylvester has.Slyvester has 35 miniature cars. How many miniature cars does Alice have? please show work

1/5= 20%

35×20%= 7. Alice has seven cars

35×20%= 7. Alice has seven cars

HIGH SCHOOL

Fred and Victoria provide the following proofs for vertical angles to be equal: A line PQ is shown cut by a transversal t. 1, 2, 3, 4 are marked clockwise as the four angles formed by the transversal on the segment PQ

Fred's proof: angle 2 + angle 3 = 180° (t is a straight line)

angle 1 + angle 2 = 180° (PQ is a straight line)

Therefore, angle 1 + angle 2 = angle 2 + angle 3 (Transitive Property of Equality)

Hence, angle 1 = angle 3 (Subtraction Property of Equality)

Victoria's proof: angle 1 + angle 4 = 180° (t is a straight line)

angle 1 + angle 2 =180° (PQ is a straight line)

Therefore, angle 1 + angle 2 = angle 1 + angle 4 (Transitive Property of Equality)

Hence, angle 2 = angle 4 (Subtraction Property of Equality)

Which statement is correct?

Both Fred's and Victoria's proofs are correct.

Both Fred's and Victoria's proofs are incorrect.

Only Fred's proof is correct.

Only Victoria's proof is correct.

Answer should be Both Fred's and Victoria's proofs are correct.

the answer is A. both fred's and victoria's proofs are correct. I just took the exam and got it right hope this helps!

MIDDLE SCHOOL

The Darnells are having a swimming pool installed. The pool has a radius of 14 feet and a height of 4 feet. What is the volume of the pool?

So a circular pool will be in the shape of a cylinder. and the formula for finding the area of a cylinder is . r=radius, h=height. If we put the numbers into the equation it is .14 squared is 196 and 4*14= 56. So our equation is now . 2*pi=6.28318530718 but let's round that to 6.283. So now our equation is much simpler 6.283(196)+6.283(56). Just multiply them. 1231.504+351.858= 1583.362 is your final answer.

MIDDLE SCHOOL

What is the solution to the equation? 2q + 18 = –5q – 3

2q+ 18= -5q -3

⇒ 2q+ 5q= -3 -18

⇒ 7q= -21

⇒ q= -21/7

⇒ q= -3

Final answer: q= -3~

⇒ 2q+ 5q= -3 -18

⇒ 7q= -21

⇒ q= -21/7

⇒ q= -3

Final answer: q= -3~

HIGH SCHOOL

Solve the system by either substitution or elimination

X-3y-3z=9

5x-3y+3z=-3

-4x+2y-4z=4

X - 3y - 3z = 9

5x - 3y + 3z = -3

--------------------add

6x - 6y = 6

x - 3y - 3z = 9.....multiply by -4

-4x + 2y - 4z = 4..multiply by 3

-------------------

-4x + 12y + 12z = -36 (result of multiplying by -4)

-12x + 6y - 12z = 12 (result of multiplying by 3)

-----------------add

-16x + 18y = - 24

6x - 6y = 6.....multiply by 3

-16x + 18y = -24

---------------------

18x - 18y = 18 (result of multiplying by 3)

-16x + 18y = -24

--------------------add

2x = - 6

x = -6/2

x = -3

6x - 6y = 6

6(-3) - 6y = 6

-18 - 6y = 6

-6y = 6 + 18

-6y = 24

y = -24/6

y = -4

x - 3y - 3z = 9

-3 - 3(-4) - 3z = 9

-3 + 12 - 3z = 9

9 - 3z = 9

-3z = 9 - 9

-3z = 0

z = 0

so ur solution is (-3,-4,0)

5x - 3y + 3z = -3

--------------------add

6x - 6y = 6

x - 3y - 3z = 9.....multiply by -4

-4x + 2y - 4z = 4..multiply by 3

-------------------

-4x + 12y + 12z = -36 (result of multiplying by -4)

-12x + 6y - 12z = 12 (result of multiplying by 3)

-----------------add

-16x + 18y = - 24

6x - 6y = 6.....multiply by 3

-16x + 18y = -24

---------------------

18x - 18y = 18 (result of multiplying by 3)

-16x + 18y = -24

--------------------add

2x = - 6

x = -6/2

x = -3

6x - 6y = 6

6(-3) - 6y = 6

-18 - 6y = 6

-6y = 6 + 18

-6y = 24

y = -24/6

y = -4

x - 3y - 3z = 9

-3 - 3(-4) - 3z = 9

-3 + 12 - 3z = 9

9 - 3z = 9

-3z = 9 - 9

-3z = 0

z = 0

so ur solution is (-3,-4,0)

MIDDLE SCHOOL

You trade 24 football card for 15 baseball card & I trade 20 football card for 32 baseball cards. Is this fair?

No this is not fair because it is not equal you have to make a fair and equal trade like the indians made in the past.

HIGH SCHOOL

the standard deviation of duration times in seconds of the old faithful geyser is less than 40 sec. identify the null hypothesis and alternative hypothesis in symbolic form

Answer:

this is a left tailed test

Null hypothesis, σ = 40 seconds

Alternate hypothesis, σ < 40 seconds.

Step-by-step explanation:

i) the standard deviation of duration times in seconds of the old faithful geyser is less than 40 sec. identify the null hypothesis and alternative hypothesis in symbolic form

ii) this is a left tailed test

Null hypothesis, σ = 40 seconds

Alternate hypothesis, σ < 40 seconds.